Решение расчетных химических задач путем формирования процедурных знаний - Нурушева, А.Б. (My University, 2013)
The article describes the types of knowledge used in educational psychology and in the course of solving computational chemistry. The algorithm for solving problems with a description of its che- mical and mathematical parts.